Applications and Achievements of Single-Cell Sequencing in Gastrointestinal Cancer - Xie, Zhenliang; Li, Jincheng; Huang, Pu; Zhang, Ye; Yang, Jingkuan; Liu, Kangdong; Jiang, Yanan (Frontiers in Oncology, 2022)
Gastrointestinal cancer represents a public health concern that seriously endangers human health. The emerging single-cell sequencing (SCS) technologies are different from the large-scale sequencing technologies which provide inaccurate data. SCS is a powerful tool for deciphering the single-cell resolutions of cellular and molecular landscapes, revealing the features of single-cell genomes, transcriptomes, and epigenomes. Recently, SCS has been applied in the field of gastrointestinal cancer research for clarifying the origin and heterogeneity of gastrointestinal cancer, acquiring micro-environmental information, and improving diagnostic and treatment methods. This review outlines the applications of SCS in gastrointestinal cancer research and summarizes the most recent advances in the field.